Conflicts in the classroom: contributions from a study on emotional self-regulation - Alarcón-Espinoza, Marina; Samper, Paula; Anguera, M. Teresa (Frontiers in Education, 2025)
To support teacher-guided techniques that support emotional self-regulation, this study characterizes how conflicts that arise in the classroom are identified and resolved. From a mixed methods perspective, nine classes were systematically observed for five sessions each. After coding the data according to an ad hoc instrument and assessing the concordance of the records, a lag sequential analysis (GSEQ5) was performed to detect the existing regularities and sequences, and a polar coordinate analysis (HOISAN) to observe the relationships among the categories. Finally, multiple cases were detected using both analysis techniques. The findings provide information on who recognizes conflicts, how they address them, and whether or not they offer solutions. The discussion emphasizes the importance of making clear how emotions are expressed, managed, and communicated and the part teachers have in educating students about them.